2016
DOI: 10.1097/ico.0000000000001092
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Corneal Subbasal Nerve Plexus in Limbal Stem Cell Deficiency

Abstract: Purpose To quantify the changes of subbasal nerve plexus in patients with limbal stem cell deficiency (LSCD) using in vivo laser scanning confocal microscopy. Design: Retrospective cross-sectional comparative study Methods Confocal images of 51 eyes of 37 patients with LSCD collected between 2010 and 2015 by the Heidelberg Retina Tomograph III Rostock Corneal Module Confocal Microscope. Two independent observers evaluated the scans of the central cornea. Seventeen normal eyes of 13 patients served as control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Other features of IVCM findings suggestive of LSCD include epithelial thinning and reduction of subbasal nerve plexus and basal cell density. [107][108][109][110]…”
Section: In Vivo Confocal Microscopymentioning
confidence: 99%
“…Other features of IVCM findings suggestive of LSCD include epithelial thinning and reduction of subbasal nerve plexus and basal cell density. [107][108][109][110]…”
Section: In Vivo Confocal Microscopymentioning
confidence: 99%
“…1I, 1N, 1S). Compared with control subjects, subbasal nerve density was reduced by 34.9% in the early stage, 54.0% in the intermediate stage, and 73.5% in the late stage of LSCD [95]. Other distinct morphologic changes of the subbasal nerve plexus in patients with LSCD include severe nerve dropout, short nerve branches, and sharp turns of the branched nerve [95].…”
Section: Recent Advances In the Diagnosis Of Lscdmentioning
confidence: 99%
“…Other quantifiable parameters such as limbal BCD, subbasal nerve density, and epithelial thickness would be necessary to establish more accurate staging of LSCD. 11,12,1417 In future investigations, the classification system could be further refined by including these quantifiable parameters. A larger prospective study would be necessary to further validate the classification system.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group has demonstrated that epithelium thickness, central cornea BCD, limbus BCD, and sub-basal nerve density are significantly decreased in eyes with LSCD and that the degree of reduction correlates with the severity of LSCD. 1517…”
Section: Introductionmentioning
confidence: 99%